2016
DOI: 10.1016/j.wem.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm and Sleep During Prolonged Antarctic Residence at Chinese Zhongshan Station

Abstract: Our results indicate that during polar nights Chinese expeditioners experienced the following problems: delayed circadian rhythm and sleep phase, later chronotype, and incidence of subsyndromal seasonal affective disorder. An appropriate combination of artificial bright light during dark winter months and a strict social schedule are recommended in a winter-over station in Antarctica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…Though participants with earlier and later circadian preferences were exposed to a similar amount of light in each site and in both time windows, in Antarctica, late chronotypes advanced their DLMO with no changes in sleep onset time and early chronotypes delayed their DLMO and sleep onset time. The behavior of late chronotypes is in line with previous observations in the Antarctic summer [66,[68][69][70] and in light manipulation experiments [35,36,73], which demonstrated the powerful circadian phase advancing effects of increasing light in the morning. In contrast, early chronotypes seem to be more responsive to the Antarctic increase in evening light exposure, which delayed their DLMO and thus prevented them from advancing their sleep start times to mitigate their strong sleep deficit.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though participants with earlier and later circadian preferences were exposed to a similar amount of light in each site and in both time windows, in Antarctica, late chronotypes advanced their DLMO with no changes in sleep onset time and early chronotypes delayed their DLMO and sleep onset time. The behavior of late chronotypes is in line with previous observations in the Antarctic summer [66,[68][69][70] and in light manipulation experiments [35,36,73], which demonstrated the powerful circadian phase advancing effects of increasing light in the morning. In contrast, early chronotypes seem to be more responsive to the Antarctic increase in evening light exposure, which delayed their DLMO and thus prevented them from advancing their sleep start times to mitigate their strong sleep deficit.…”
Section: Discussionsupporting
confidence: 90%
“…In the long nights of the Antarctic winter, for example, there is no light information to suppress melatonin levels and thus to set circadian time. Therefore, two lines of evidence arise from Antarctic seasonal studies: 1) Daytime melatonin levels are significantly higher in the Antarctic winter than in the summer [66,67], and 2) the melatonin rhythm is delayed in the winter with respect to the summer [66,[68][69][70][71][72]. In addition, a long series of studies conducted in the small overwintering community of the British Halley Research Station demonstrated that the winter delay in the melatonin rhythm can be advanced to the summer phase by bright light treatment [73].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, expeditioners suffer from sensory deprivation by a monotone environment with lack of stimuli, restricted food variation, and a distinct social narrowing with high potential for conflicts ( Das et al, 2018 ). Furthermore, a disruptive circadian rhythm may influence the hormonal stress response ( Chen et al, 2016 ; Vitale et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, total time slept, together with sleep efficiency and latency, did not change in 17 winter-over crewmembers at the Chinese Zhonshang station (Chen et al, 2016). The authors reported a delay of sleep onset, offset, a mid-sleep time in Antarctica compared to a pre-departure measurement, with a peak in midwinter for sleep onset and before and in mid-winter in the other time-points compared to the baseline and to the end of winter (Chen et al, 2016). Delay in sleep timing, and an increase in sleep fragmentation, were also found in winter by Francis et al (2008).…”
Section: Polar Environmentsmentioning
confidence: 83%
“…However, even in this case, the summertime point was the last month of the Antarctic period, and possible effects other than photoperiod might be present. Instead, total time slept, together with sleep efficiency and latency, did not change in 17 winter-over crewmembers at the Chinese Zhonshang station (Chen et al, 2016). The authors reported a delay of sleep onset, offset, a mid-sleep time in Antarctica compared to a pre-departure measurement, with a peak in midwinter for sleep onset and before and in mid-winter in the other time-points compared to the baseline and to the end of winter (Chen et al, 2016).…”
Section: Polar Environmentsmentioning
confidence: 89%